INTERAKSI SOSIAL DOSEN DAN MAHASISWA DALAM PROSES PERKULIAHAN DI JURUSAN PPKN FIS UNIMA - Pangalila, Theodorus (PKn Progresif, 2017)
ABSTRACTThis research is motivated by the problems of education in Indonesia which is a very urgent thing. Many problems faced the world of education in Indonesia, ranging from the problems of human resources (HR) teachers and lecturers to the education system as a whole. The purpose of this study is to determine the process of interaction between lecturers and students in the learning process in the department of PPKn FIS Unima and the factors that influence the interaction process. This research is a type of qualitative research with the data source is lecturer and student in the department of PPKn FIS Unima. Data collection techniques used in this study are observation and interview. The main theory used in this research is the theory of interaction supported by concepts such as the concept of lecturers and students. From the results of this study obtained the conclusion that the process of interaction of lecturers and students in the learning process in the department of PPKn running well and there are important factors that influence the interaction process. This research recommends further research in relation to factors influencing lecturer and student interaction process. Keywords: Process, Interaction, Lecturer, Student